Self-suspension modified magnesium hydroxide flame retardant as well as preparation method and application thereof
The preparation method of self-suspending modified magnesium hydroxide flame retardant solves the problems of poor flame retardant effect and easy sedimentation of conventional magnesium hydroxide in water-based polyurethane coatings, realizes stable suspension and high-efficiency flame retardancy of modified magnesium hydroxide in water-based polyurethane coatings, and improves the environmental protection and performance of the coatings.
Patent Information
- Application Number
- CN202511317505.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-09-16
AI Technical Summary
When conventional magnesium hydroxide is used as a flame retardant for waterborne polyurethane coatings, it has poor flame retardant effect, is easy to settle, and its strong alkalinity affects the stability of the coating.
A preparation method for self-suspended modified magnesium hydroxide flame retardant is adopted. Through layer-by-layer self-assembly technology and bridging additives such as polyetheramine and polyvinyl pyrrolidone, a double-layer coated magnesium hydroxide shell-core structure is formed. The hydration and swelling effect of the sodium bentonite flakes is utilized to achieve stable suspension, and the flame retardancy and smoke suppression properties are improved through the silicate shell layer.
The modified magnesium hydroxide is autonomously dispersed and suspended in waterborne polyurethane coatings, remains stable for a long time without settling, improves flame retardancy and smoke suppression, reduces the amount of magnesium hydroxide added, and maintains the stability of the coating.
Smart Images

Figure CN120795674A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of flame-retardant material preparation, in particular to a self-suspension modified magnesium hydroxide flame retardant, a preparation method and application thereof. BACKGROUND
[0002] Waterborne polyurethane coating is a kind of coating with waterborne polyurethane resin as base material and water as dispersion medium, which has good storage stability, film mechanical properties, water resistance, solvent resistance and aging resistance, and has been widely used in the field of waterborne coatings. However, the flame-retardant effect of waterborne polyurethane coating itself is poor, so the research on improving the flame-retardant effect of waterborne polyurethane coating has become a research hotspot in recent years.
[0003] The current technical implementation mainly achieves the flame-retardant requirement by directly adding flame retardants in the coating. The commonly used high-efficiency flame-retardant coating contains halogen. When the halogen-containing material burns, a large amount of toxic smoke, carbon monoxide, hydrogen halide and other corrosive gases are released, thereby hindering the evacuation and fire extinguishing work of people in the fire, causing "secondary" pollution after the fire, and causing great loss of life and property. The world attaches great importance to the environmental protection problem of flame-retardant coating, so halogen-free flame-retardant coating has become the development trend of coating.
[0004] The flame-retardant additive used in the commonly used halogen-free flame-retardant coating is conventional aluminum hydroxide, magnesium hydroxide, silicate and expanded graphite system. Magnesium hydroxide stands out due to cost and resource advantages. When the conventional magnesium hydroxide is used as an additive, its flame-retardant rate is low, the compatibility with organic components is poor, the required filling amount is large, and the flame-retardant effect can be achieved only when the filling amount is more than 50% of the total weight of the coating. Moreover, hard or soft settling easily occurs, which brings great difficulty to the use after long-term transportation. Moreover, the medium-strong alkaline nature of magnesium hydroxide easily leads to imbalance of the stability of waterborne polyurethane coating, and a plurality of chemical additives need to be added to improve the use performance of the coating, which greatly reduces the environmental protection of waterborne coating and limits its development and application. SUMMARY
[0005] The present application aims to provide a self-suspension modified magnesium hydroxide flame retardant, a preparation method and application thereof, so as to solve the technical problems of poor flame-retardant effect and easy settling of conventional magnesium hydroxide as an additive mentioned in the background.
[0006] To achieve the above-mentioned purpose, the present application provides the following technical solutions: The present application provides a preparation method of a self-suspension modified magnesium hydroxide flame retardant, comprising the following steps: (1) obtaining magnesium hydroxide filter cake A; (2) dispersing the magnesium hydroxide filter cake A into magnesium hydroxide slurry with a solid content of 10-15%, and adding KH560 and titanate coupling agent to modify the slurry to obtain slurry B; (3) dispersing attapulgite, adding CTAB solution to modify a colloid C; (4) adding the slurry B to the colloid C to stir; (5) adding a crosslinking agent to the stirring solution of step (4), and filtering and drying to obtain a coated modified magnesium hydroxide M; (6) dispersing the magnesium hydroxide M into a magnesium hydroxide slurry D; (7) taking sodium-based bentonite modified by PAAS to shear to obtain a dispersion F; (8) adding the magnesium hydroxide slurry D to the dispersion F to mix, adding PVP K30 to stir; (9) spray drying to obtain a magnesium hydroxide flame retardant.
[0007] In a preferred embodiment, in step (1), a magnesium hydroxide slurry is filtered, washed with water, and then a magnesium hydroxide filter cake A is obtained, wherein the particle size of the magnesium hydroxide is 0.8-1.2 μm.
[0008] In a preferred embodiment, in step (3), the length of the attapulgite is 0.96-2.4 μm, and the particle size is 40-120 nm.
[0009] In a preferred embodiment, in step (4), the pH of the slurry B and the colloid C is first adjusted to 9-10, and then the slurry B is added to the colloid C to stir.
[0010] In a preferred embodiment, in step (4), the mass ratio of the slurry B to the colloid C is 4-5:1; and in step (8), the mass ratio of the magnesium hydroxide slurry D to the dispersion F is 2-4:1.
[0011] In a preferred embodiment, in step (6), a polydopamine coating layer is coated on the surface of the magnesium hydroxide M.
[0012] In a preferred embodiment, in step (7), the sodium-based bentonite has a small-size lamellar structure with a diameter of <100 nm.
[0013] In a preferred embodiment, in step (9), silica aerogel is added during the spray drying process.
[0014] The second aspect of the present application provides a self-suspension modified magnesium hydroxide flame retardant prepared by the above preparation method.
[0015] The third aspect of the present application provides a halogen-free flame-retardant water-based polyurethane coating, comprising: a water-based polyurethane resin, the modified magnesium hydroxide flame retardant, a dispersing agent, a defoaming agent and a mildew-proof agent, and the mass ratio of the water-based polyurethane resin, the modified magnesium hydroxide flame retardant, the dispersing agent, the defoaming agent and the mildew-proof agent is (50-70):(32-36):(1-2):(0-1):(0-1).
[0016] Compared with the prior art, the present application has the following advantages: the self-suspension modified magnesium hydroxide flame retardant provided by the present application has thixotropy, and when applied to water-based polyurethane coating, it can realize self-dispersing suspension without adding other anti-settling agents, can achieve 6 months without water separation, and the outer coating layer is a silicate-based weak alkaline compound, which solves the problem of the influence of the high pH value of magnesium hydroxide on the stability of water-based polyurethane, and further improves the flame retardance and smoke suppression of water-based polyurethane, specifically: (1) The self-suspension modified magnesium hydroxide flame retardant provided by the present application realizes the stable shell-core structure of double-layer coated magnesium hydroxide by using layer-by-layer self-assembly technology and effective bridging agents such as polyetheramine and polyvinylpyrrolidone, and when used in water-based polyurethane coating, the outermost sodium-based bentonite layer can thicken the emulsion through the hydration swelling effect of the sheet layer, and has the effect of long-term stable suspension and non-settling; by coating a layer of polydopamine coating on the surface of the intermediate product magnesium hydroxide M and controlling the size of the bentonite sheet layer, the damage of the swelling effect of the outer coating layer to the stable shell-core structure is avoided. (2) Under the support of the two thixotropic shell layers, the modified magnesium hydroxide also has thixotropy, which can realize good dispersion and stable suspension and non-settling in water-based polyurethane coating and other water-based resins, thereby breaking the application limitation of magnesium hydroxide; (3) Under the action of the two silicate-based shell layers, the flame retardance and smoke suppression of magnesium hydroxide are greatly improved, thereby reducing the addition amount of magnesium hydroxide; (4) The double-layer coated magnesium hydroxide can also effectively avoid the damage of the medium-strong alkalinity of magnesium hydroxide to the stability of water-based polyurethane coating. The pH value of unmodified magnesium hydroxide is large, and a large amount of addition can easily lead to imbalance of the stability of water-based polyurethane, resulting in gel demulsification. The modified magnesium hydroxide of the present application has a pH value close to that of water-based polyurethane after being dispersed in the water-based system, so it does not affect the system stability. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 The settling state of the water-based polyurethane coating prepared in Example 3 of the present application after being placed for 6 months; Figure 2 The settling state of the water-based polyurethane coating prepared in Comparative Example 2 of the present application after being placed for 2 days. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.
[0019] The present application provides a preparation method of self-suspension modified magnesium hydroxide flame retardant, comprising the following steps: First step: using hydrothermal reaction to prepare magnesium hydroxide slurry, filtering and washing with water for multiple times to obtain magnesium hydroxide filter cake A; in this step, the particle size of magnesium hydroxide is 0.8-1.2 μm, and the crystal morphology is regular hexagonal flake, and the pH after washing is 9-10; Second step: dispersing magnesium hydroxide filter cake A with deionized water at high speed to prepare magnesium hydroxide slurry with solid content of 10-15%, continuing to disperse at high speed, and adding modifier to the magnesium hydroxide slurry at 60°C, wherein the modifier is a mixture of KH560 (silane coupling agent) and titanate coupling agent, and the total amount of the modifier is 1%-2% of the mass of the magnesium hydroxide slurry; Modifying for 1 h to obtain modified slurry B, and the mass ratio of KH560 to titanate coupling agent is 3:1; Third step: dispersing attapulgite in deionized water at high speed to obtain a stable colloid C, wherein the length of attapulgite is 0.96-2.4 μm, and the particle size range is 40-120 nm; at the same time, 1% of CTAB contains 0.1% of polyacrylic acid sodium in terms of mass; Fourth step: adding an appropriate amount of auxiliary to adjust the pH of slurry B and colloid C to 9-10, then slowly adding slurry B into colloid C, and stirring at 60°C-70°C for 2 h; The auxiliary is one of NaOH, tetramethylammonium hydroxide and sodium carbonate, and the mass ratio of slurry B to colloid C is 4-5:1; Fifth step: adding a crosslinking agent (0.8% of aluminum chloride or polyetheramine D230 in terms of mass of the solution) into the solution formed in the fourth step, and then drying after filtering and washing for multiple times to obtain coated modified magnesium hydroxide M; Sixth step: dispersing the magnesium hydroxide M after oxidizing and self-polymerizing a layer of polydopamine coating on the surface of the magnesium hydroxide M to prepare magnesium hydroxide slurry D with solid content of 10%; Step 7: Sodium bentonite is prepared into a dispersion liquid with a solid content of 10% by adding water, modified by sodium polyacrylate (PAAS, industrial grade, brand: Karamar) with a solid mass of 2% of sodium bentonite, and prepared into a nanometer layer dispersion liquid F by high-speed shearing (10000 rpm, 20 min); The sodium bentonite is obtained by centrifugal classification and has a small-size lamellar structure with a diameter of less than 100 nm; Step 8: The magnesium hydroxide slurry D is slowly added into the dispersion liquid F, the mass ratio of the magnesium hydroxide slurry D to the dispersion liquid F is 2-4:1, the pH of the mixed liquid is adjusted to 7.0, 0.1% of polyvinylpyrrolidone (PVP K30) is added into the mixed liquid as a hydrogen bond mediator, and the mixed liquid is stirred at a low speed (200 rpm) at 40℃ for 4 h; Step 9: The liquid formed in Step 8 is spray dried, 3% of silica aerogel is added to prevent caking, and a double-layer modified magnesium hydroxide flame retardant with a stable shell-core structure is obtained after drying.
[0020] The present application solves the problem of preventing magnesium hydroxide from settling by comprehensively considering viscosity, particle size, electrostatic effect and thixotropic mechanism. 1. The pH value of the magnesium hydroxide treated by the modifier and the attapulgite treated by CATB is about 8, and they are positively charged, which is not conducive to interlamellar adsorption. The present application adjusts the pH value of the attapulgite dispersion liquid to be negatively charged by a pH adjusting aid, realizes electrostatic coating, and adds an interfacial bridging agent polyetheramine to form a Si-O-C-NH- covalent network between the epoxy group of KH560 and the -SiOH in the attapulgite, so as to realize a stable shell structure. The addition of titanate coupling agent can more completely and densely coat the surface of magnesium hydroxide in cooperation with KH560. Meanwhile, the outer shell is coated with a layer of polydopamine coating to enhance the stability of the shell-core, so that the water in the outermost layer does not further infiltrate under swelling, and the stability of the double-layer shell-core structure is ensured.
[0021] 2. The size of the attapulgite and bentonite selected in the present application is nanoscale, which is easy to agglomerate and affects the coating effect. In the present application, high-speed shearing is used for dispersion, polyvinylpyrrolidone is added as a hydrogen bond mediator during the reaction process to effectively bridge the attapulgite and bentonite; during the drying process, silica aerogel is synchronously added as a nanometer support to maintain the pore structure, prevent the collapse of the shell-core structure during the drying process, and prevent the agglomeration and caking of the materials.
[0022] The application further provides a halogen-free flame-retardant water-based polyurethane coating, comprising a flame-retardant filler, a water-based polyurethane resin, a dispersing agent, a defoaming agent and a mildew-proof agent, wherein the flame-retardant filler is the self-suspension modified magnesium hydroxide flame retardant prepared by the preparation method, and the mass ratio of the water-based polyurethane resin, the modified magnesium hydroxide flame retardant, the dispersing agent, the defoaming agent and the mildew-proof agent is (50-70):(32-36):(1-2):(0-1):(0-1).
[0023] The application will be further described in detail below in combination with the examples, and it should be understood that the following examples are only used to further illustrate the application and cannot be understood as limiting the protection scope of the application. Some non-essential improvements and adjustments made by the person skilled in the art according to the above content of the application all belong to the protection scope of the application. The specific process parameters in the following examples are only one example in the appropriate range, i.e. the person skilled in the art can make appropriate selection in the range through the description herein, and not limited to the specific values in the following examples.
[0024] In the following examples, the raw materials used are commercially available, and the processes used are conventional processes, unless otherwise specified.
[0025] Example 1
[0026] The preparation method of the self-suspension modified magnesium hydroxide flame retardant provided in the example includes the following steps: First step: using hydrothermal reaction to prepare hexagonal flake-shaped magnesium hydroxide slurry with a particle size of 0.8-0.9 μm, filtering and washing with water for multiple times, measuring the pH value to be 10, and obtaining magnesium hydroxide filter cake A; Second step: dispersing the magnesium hydroxide filter cake A with deionized water at high speed to prepare magnesium hydroxide slurry with a solid content of about 10%, continuing to disperse at high speed, adding 1% of a mixture of KH560 and titanate coupling agent at 60°C, modifying for 1 h, and obtaining modified slurry B; Third step: dispersing attapulgite (length 0.96 μm, diameter 40 nm) in deionized water at high speed, with a solid content of 10%, adding 1% of CTAB (cetyltrimethylammonium bromide), and modifying for 2 h at 60°C to form stable colloid C; Fourth step: adding 1% of tetramethylammonium hydroxide with a concentration of 1.5 mL / g to adjust the pH value of the slurry B and the colloid C to 9, then slowly adding the slurry B into the colloid C, and stirring at 60°C-70°C for 2 h with the mass ratio of the slurry B to the colloid C being 4:1; Fifth step: adding a crosslinking agent (0.8% of polyetheramine D230 in the solution) to the solution in the fourth step, filtering, washing for multiple times, and drying to obtain the coated modified magnesium hydroxide M; Sixth step: after the surface of magnesium hydroxide M is oxidized and self-polymerized to form a polydopamine coating, water is added for dispersion to prepare a magnesium hydroxide slurry D with a solid content of 10%; Seventh step: sodium bentonite (diameter <100 nm) is added with water to prepare a dispersion liquid with a solid content of 10%, which is modified with 2% sodium polyacrylate (PAAS) and sheared at a high speed (10000 rpm, 20 min) to prepare a nanolayer dispersion liquid F; Eighth step: the magnesium hydroxide slurry D is slowly added to the dispersion liquid F, the mass ratio of the slurry D to the dispersion liquid F is 3:1, the pH is adjusted to 7.0, 0.1% polyvinylpyrrolidone (PVP K30) is added as a hydrogen bond mediator, and the mixture is stirred at a low speed (200 rpm) at 40°C for 4 h. Ninth step: spray drying, adding 3% silica aerogel for anti-caking, and obtaining a double-layer modified magnesium hydroxide flame retardant with a stable shell-core structure after drying.
[0027] The embodiment also provides a halogen-free flame-retardant waterborne polyurethane coating, which comprises waterborne polyurethane resin, modified magnesium hydroxide flame retardant, dispersant, defoaming agent and mildew-proof agent in a mass ratio of 60:35:2:1:1, and is uniformly stirred with a high-speed dispersant to obtain the halogen-free flame-retardant waterborne polyurethane coating.
[0028] Example 2
[0029] The embodiment differs from example 1 in that the first step is to prepare a hexagonal flaky magnesium hydroxide slurry with a particle size of 1.0-1.1 μm; and the third step is to use attapulgite with a length of 1.2 μm and a diameter of 80 nm.
[0030] The halogen-free flame-retardant waterborne polyurethane coating provided by the embodiment comprises waterborne polyurethane resin, modified magnesium hydroxide flame retardant, dispersant, defoaming agent and mildew-proof agent in a mass ratio of 70:32:1:1:1, and is uniformly stirred with a high-speed dispersant to obtain the halogen-free flame-retardant waterborne polyurethane coating.
[0031] Example 3
[0032] The embodiment differs from example 1 in that the first step is to prepare a hexagonal flaky magnesium hydroxide slurry with a particle size of 1.1-1.2 μm; and the third step is to use attapulgite with a length of 2.4 μm and a diameter of 120 nm.
[0033] The halogen-free flame-retardant waterborne polyurethane coating provided by the embodiment comprises waterborne polyurethane resin, modified magnesium hydroxide flame retardant, dispersant, defoaming agent and mildew-proof agent in a mass ratio of 50:36:1:1:1, and is uniformly stirred with a high-speed dispersant to obtain the halogen-free flame-retardant waterborne polyurethane coating.
[0034] Example 4
[0035] The difference between the present example and Example 1 is that the pH regulator in the fourth step is NaOH with a concentration of 0.6 mL / g.
[0036] The halogen-free flame-retardant water-based polyurethane coating provided by the present example comprises water-based polyurethane resin, modified magnesium hydroxide flame retardant, dispersant and defoaming agent in a mass ratio of 60:35:2:1, and the halogen-free flame-retardant water-based polyurethane coating is obtained by stirring uniformly with a high-speed dispersant.
[0037] Example 5
[0038] The difference between the present example and Example 1 is that the pH regulator in the fourth step is Na2CO3 with a concentration of 2.0 mL / g.
[0039] The halogen-free flame-retardant water-based polyurethane coating provided by the present example comprises water-based polyurethane resin, modified magnesium hydroxide flame retardant, dispersant and defoaming agent in a mass ratio of 60:35:2:1, and the halogen-free flame-retardant water-based polyurethane coating is obtained by stirring uniformly with a high-speed dispersant.
[0040] Example 6
[0041] The difference between the present example and Example 1 is that in the fourth step, the mass ratio of slurry B to colloid C is 5:1.
[0042] Comparative Example 1 The difference between the present comparative example and Example 1 is that in the first step, a hexagonal flake-shaped magnesium hydroxide slurry with a particle size of 5 μm is prepared.
[0043] Comparative Example 2 The difference between the present comparative example and Example 1 is that in the third step, the length of the attapulgite is 10 μm and the diameter is 500 nm.
[0044] Comparative Example 3 The difference between the present comparative example and Example 1 is that in the fourth step, no pH regulating aid is added.
[0045] Comparative Example 4 The difference between the present comparative example and Example 1 is that in the fifth step, no crosslinking agent polyetheramine is added.
[0046] Comparative Example 5 The difference between the present comparative example and Example 1 is that in the sixth step, the surface of the magnesium hydroxide M product is not coated with a polydopamine coating.
[0047] Comparative Example 6 The difference between the present comparative example and Example 1 is that in the fourth step, the mass ratio of slurry B to colloid C is 8:1, and in the eighth step, the mass ratio of slurry D to dispersion F is 6:1.
[0048] The halogen-free flame-retardant waterborne polyurethane coating prepared in Examples 1-6 and Comparative Examples 1-6 was taken in part and placed in a 60°C oven for 7 days, and whether there was sedimentation or water separation was observed; a part was poured into an oxygen index and vertical combustion sample mold, and after curing, it was taken out for testing, the oxygen index detection standard was GB / T 2406.2-2009; the vertical combustion grade detection standard was the UL94 flame-retardant grade standard, and the observation and test results are shown in Table 1.
[0049] Table 1 Test results of the halogen-free flame-retardant waterborne polyurethane coating obtained in Examples 1-6 and Comparative Examples 1-6
[0050]
[0051] Comparative analysis of the test data in Table 1 shows that the halogen-free flame-retardant waterborne polyurethane coating obtained by the examples of the present application has good suspension stability, and the good core-shell structure is conducive to improving the flame retardance and smoke suppression.
[0052] In Comparative Example 1, the magnesium hydroxide with a large particle size and a small specific surface area was used, which caused the coupling agent to be poorly anchored and the coating material to be insufficiently covered, and the defects in the core-shell structure led to sedimentation and low flame-retardant efficiency.
[0053] In Comparative Example 2, the size of the attapulgite was too large, on the one hand, the specific surface area was too small, and the magnesium hydroxide core could not be completely wrapped; on the other hand, the large size of the rod material was more rigid, and it was difficult to tightly wrap around the smaller magnesium hydroxide particles, resulting in holes and unevenness in the coating layer, and a loose structure.
[0054] In Comparative Example 3, the pH of the slurry B and the colloid C in the fourth step was not adjusted, so that both of them were positively charged, repelled by the electric charge, not conducive to interlayer adsorption, and further led to unstable inner core-shell structure, hard sedimentation, and poor flame-retardant and smoke suppression effect.
[0055] In Comparative Example 4, no crosslinking agent polyetheramine was added in the fifth step, the shell structure did not form a covalent network, the coating layer was easy to fall off, and the stability was poor.
[0056] In Comparative Example 5, the surface of the magnesium hydroxide M product was not coated with a polydopamine coating in the sixth step, and under the swelling of the outermost layer, water infiltrated, causing damage to the stable core-shell structure, leading to soft sedimentation.
[0057] In Comparative Example 6, the relative content of the magnesium hydroxide slurry in the fourth step and the eighth step was set too high, the proportion was unbalanced, and further caused the coating layer structure to be incomplete, affecting the suspension and the flame-retardant effect.
[0058] The above shows and describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited to the above-mentioned embodiments, and the above-mentioned embodiments and descriptions in the specification are only preferred examples of the present application and are not intended to limit the present application. Various changes and improvements can be made to the present application without departing from the spirit and scope of the present application, and these changes and improvements all fall within the scope of the claimed present application. The scope of protection of the present application is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a self-suspending modified magnesium hydroxide flame retardant, characterized in that: The following steps are involved: (1) Obtaining magnesium hydroxide filter cake A; (2) Dispersing magnesium hydroxide filter cake A into magnesium hydroxide slurry with a solid content of 10-15%, adding KH560 and titanate coupling agent to modify the slurry to obtain slurry B; (3) Dispersing attapulgite and adding CTAB solution to modify it to obtain colloid C; (4) adding the slurry B into the colloid C and stirring; (5) adding a crosslinking agent to the stirred solution of step (4), filtering, and drying to obtain coated modified magnesium hydroxide M; (6) dispersing the magnesium hydroxide M into magnesium hydroxide slurry D; (7) Sodium bentonite modified with PAAS was sheared to obtain dispersion F; (8) Add magnesium hydroxide slurry D to dispersion F and mix, then add PVP K30 and stir; (9) Spray drying to obtain magnesium hydroxide flame retardant.
2. The preparation method of the self-suspending modified magnesium hydroxide flame retardant according to claim 1, wherein In step (1), magnesium hydroxide slurry is filtered and washed with water to obtain magnesium hydroxide filter cake A, wherein the particle size of the magnesium hydroxide is 0.8-1.2 μm.
3. The preparation method of the self-suspending modified magnesium hydroxide flame retardant according to claim 1, wherein In step (3), the length of the attapulgite is 0.96-2.4 μm, and the particle size is 40-120 nm.
4. The preparation method of the self-suspending modified magnesium hydroxide flame retardant according to claim 1, wherein In step (4), the pH of the slurry B and the colloid C is first adjusted to 9-10, and then the slurry B is added to the colloid C and stirred.
5. The method for preparing the self-suspending modified magnesium hydroxide flame retardant according to claim 4, wherein: In step (4), the mass ratio of the slurry B to the colloid C is 4-5:1; in step (8), the mass ratio of the magnesium hydroxide slurry D to the dispersion F is 2-4:
1.
6. The preparation method of the self-suspending modified magnesium hydroxide flame retardant according to claim 1, wherein In step (6), a polydopamine coating is applied on the surface of the magnesium hydroxide M.
7. The preparation method of the self-suspending modified magnesium hydroxide flame retardant according to claim 1, wherein In step (7), the sodium bentonite has a small-sized lamellar structure with a diameter of <100 nm.
8. The preparation method of the self-suspending modified magnesium hydroxide flame retardant according to claim 1, wherein In step (9), silica aerogel is added during the spray drying process.
9. A self-suspending modified magnesium hydroxide flame retardant prepared by the preparation method according to any one of claims 1 to 8.
10. A halogen-free flame-retardant water-based polyurethane coating, characterized in that: include: The water-based polyurethane resin, the modified magnesium hydroxide flame retardant according to claim 9, the dispersant, the defoamer and the mildew preventer, wherein the mass ratio of the water-based polyurethane resin, the modified magnesium hydroxide flame retardant, the dispersant, the defoamer and the mildew preventer is (50-70):(32-36):(1-2):(0-1):(0-1).
Citation Information
Patent Citations
Flame-retardant rubber material
CN110862621A
Antibacterial flame-retardant high-viscosity polyethylene film as well as preparation method and application thereof
CN114874523A
Flame-retardant polyolefin cable insulating material and preparation method thereof
CN118978756A
Flame-retardant medium-voltage power cable
CN120473232A
Composite magnesium hydroxide particle, flame retardant composition and flame-retardant polyolefin resin composition
JP2010030882A
Cited By
High-rheology lasting coating and preparation method thereof
CN121673919A